2014
DOI: 10.1002/2014jd021920
|View full text |Cite
|
Sign up to set email alerts
|

Improving satellite‐driven PM2.5 models with Moderate Resolution Imaging Spectroradiometer fire counts in the southeastern U.S.

Abstract: Multiple studies have developed surface PM 2.5 (particle size less than 2.5 μm in aerodynamic diameter) prediction models using satellite-derived aerosol optical depth as the primary predictor and meteorological and land use variables as secondary variables. To our knowledge, satellite-retrieved fire information has not been used for PM 2.5 concentration prediction in statistical models. Fire data could be a useful predictor since fires are significant contributors of PM 2.5 . In this paper, we examined whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 28 publications
0
24
1
Order By: Relevance
“…Liu et al, 2007;Wang & Christopher, 2003). Many studies have proposed statistical models using AOD to predict PM 2.5 concentrations (X. F. Hu et al, 2014b;X. F. Hu, Waller, Lyapustin, Wang, Al-Hamdan, et al, 2014;Kloog et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al, 2007;Wang & Christopher, 2003). Many studies have proposed statistical models using AOD to predict PM 2.5 concentrations (X. F. Hu et al, 2014b;X. F. Hu, Waller, Lyapustin, Wang, Al-Hamdan, et al, 2014;Kloog et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Statistical models have obtained good performance in PM 2.5 exposure estimation in the eastern part of the United States (X. F. Hu et al, 2014b;X. F. Hu, Waller, Lyapustin, Wang, Al-Hamdan, et al, 2014;Kloog et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To improve accuracy, we considered fire emissions in the GWR model development process as previous studies have reported that biomass burning can affect AOD-PM2.5 relations [23,26]. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggested that remotely sensed fire count data could improve PM2.5 prediction accuracy, and will have good prediction power when the buffer zone reach 50km. [30] To capture fire emissions, we used number of fire spots within 10 buffer lengths from 5km to 100km using Moderate-resolution Imaging Spectroradiometer (MODIS) Global Monthly Fire Location Product (MCD14ML) [31].…”
Section: Geographical Predictorsmentioning
confidence: 99%